Development of an integrated web-based indoor parking system with sensors - M. Hamed, Mosaab; A. lATIFF, LIZA; A. Kamil, Izzaty; Dziyauddin, Rudzidatul Akmam; MAD KAIDI, HAZILAH (International Journal of Integrated Engineering, 2018)
Growing number of vehicles in recent years has an impact to road capacity and parking spaces. Even with support of an efficient public transport, some users prefer to use their personal vehicles. Hence, it resulted in lack of parking space in public areas. Looking for parking spaces is time, money and fuel consuming and causes unnecessary stress to drivers. This work will design and develop the sensing infrastructure which will be used as a part of an integrated smart parking system that integrates the sensing capability with wireless transmission to the central web portal. Then, the central web portal will provide a platform for vehicle parking reservation system made online through a computer. This system also permits drivers to make a reservation on available parking slots utilizing ID code keyed in for authentication and several indicators to denote availability, non-availability and reservation status at the parking slot. The communication technologies used has to upload and download information to and from the web. This work has shown that the development was successful for a single floor parking system and can be upgraded to multi-storey parking complex.